(3GdJgGH fjQGf GdCMRGf heKjQ GdcBHI hGdCTLGfs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg (B... (3abO bQCJ aj GdcJH hGdCNHGQ hJUaMJ aj (B... (3hhbaJ Ydi NHQ JGe eJVef dhaGI QShd Gddg Udi Gddg Ydjg hSde (B...(3Pdc aj cJH eJYOOI (B...s
(3BNQgG (B:s
.... (3EdG HYO GdGSJZGQ hGdJhHI hh Cf bQjTG JGHJ Edj hGYJPQJ ef aYdgG dOj dcfJ GSJZaQJ Gddg dge haj gPG GdbOQ caGjIs
(3JHUQI GdYfhGf (B:s
(3hjbGd dg GdJgGH GdCMRGf aj haGI SjO Hfj YOfGf GdeHYhK Ydi GdEfS hGdLGf QShd Gdedc GdefGf, heG ChUi Hg aj Mb Cgd HjJg CefGA GdQMef, heG LQi HYO haGJg ef GdGNJdGa hGdNPdGfs
(3JHUQI GdeDda (B:s
(3WHY efShHG d` (B: (3MSjf Hf eMeO Hf CMeO Hf YUahQ GdOQGRj GdHMQjfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B2 - 162 ( 1164)s
Keywords: (3GdJGQjNs